Pengaruh model pembelajaran orientation challenge apply review terhadap kemampuan menulis puisi cinta lingkungan peserta didik kelas v sekolah dasar - Febiana Putri Khasanah; Septi Yulisetiani (Didaktika Dwija Indria, 2025)
This study aims to determine the effect of the OCAR (Orientation, Challenge, Apply, Review) learning model on the ability to write environmental poetry of fifth-grade elementary school students. The method used is an experiment with a pretest-posttest control group design. The research sample consisted of two classes, namely the experimental class using the OCAR learning model and the control class using the CIRC (Cooperative Integrated Reading and Composition) learning model. Data were collected through poetry writing tests and observations of the implementation of learning. The results showed that there was a significant increase in poetry writing ability in the experimental class compared to the control class. The average posttest score of the experimental class reached 82.15, while the control class was 72.52. The t-test produced a t-value of 3.650 > t-table 2.007, which means there is a significant difference between the two classes. The increase in students' abilities is seen in the indicators of message, diction, style, typography, and title. However, the theme indicator experienced a decline. These findings indicate that the OCAR learning model is effective in improving poetry writing skills while forming students' environmental awareness.